How Does U.S. Monetary Policy Influence Economic Conditions in Emerging Markets? - Arora, Vivek (IMF Working Papers; Working Paper, 2000)
This paper quantifies the economic impact of changes in U.S. monetary policy on emerging market countries. We explore empirically how country risk, as proxied by sovereign bond spreads, is influenced by U.S. monetary policy, country-specific fundamentals, and conditions in global capital markets. In addition, we simulate the direct effects of a tightening in U.S. monetary policy on economic conditions in developing countries. While country-specific fundamentals are important in explaining fluctuations in country risk, the stance and predictability of U.S. monetary policy are also important for stabilizing capital flows and capital market conditions and fostering economic growth in developing countries.